ANALISIS KELAYAKAN E-LKPD BERBASIS COLLABORATIVE LEARNING PADA MATERI DAUR BIOGEOKIMIA DALAM MELATIH KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK - Sa’adatud Daroini Rahmania; Winarsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the feasibility of Collaborative Learning-based E-LKPD in the biogeochemical cycle sub-material in training the critical thinking skills of class X students of SMA Negeri 8 Surabaya, reviewed from the aspects of validity, practicality, and effectiveness. This study uses a descriptive method with a quantitative approach in research and development design. The research subjects consisted of 20 students of class X. Data collection techniques were carried out through expert validation sheets, observation sheets on learning implementation, student response questionnaires, and critical thinking ability tests (pretest-posttest) which included six indicators, namely interpretation, analysis, inference, explanation, evaluation, and self-regulation. The data was analyzed descriptively in the form of percentages categorized based on interpretation criteria. The results of the study showed that E-LKPD was declared very valid with an average score of 97.92%, very practical with a learning implementation percentage of 97.75% and student response of 98%, and effective in training students' critical thinking skills, as shown by the increase in the achievement of critical thinking indicators from 71.46% (pretest, fairly good category) to 93.13% (posttest, the category is very good), with all 20 students declared complete in the posttest. Thus, Collaborative Learning-based E-LKPD on the biogeochemical cycle sub-material is declared feasible to train students' critical thinking skills.